Conference 2014: Promoting Today's Ideas for Tomorrow's Medicine: Pharmaceutical Science to Regulatory Science. An international symposium held jointly by CSPS and CC-CRS, June 10-13, 2014, Montreal, QC, Canada - Canadian Society for Pharmaceutical Sciences (CSPS) (Frontiers Media S.A., 2014)
Plenaries and Special Presentations: Supriya Sharma, Acting Associate Assistant Deputy Minister, Health Canada:  "Facing Tomorrow's Regulatory Challenges Today" Mick Bhatia, McMaster Stem Cell and Cancer Research Institute (SCC-RI): "Potential Applications of Human Stem Cells in Therapeutics" You Han Bae, University of Utah: "Current Paradigm of Cancer Nanomedicine and its Perspective - A Gap Between Experimental & Clinical Worlds" Laszlo Endrenyi, University of Toronto: CSPS Lifetime Achievement Award - "Sense and Sensibility (?) in Science" Rav Kumar, GlaxoSmithKline: CSPS Award of Leadership in Canadian Pharmaceutical Sciences - "A Bright Future for Pharmaceutical Sciences in Canada" Emmanuel Ho, University of Manitoba: GlaxoSmithKline/CSPS Early Career Award - "Development of Intravaginal Microbicides for the Prevention of HIV Infection" Building Opportunity Day: - The Life Sciences Industry in Canada:  Now and the Future... - Start-up Pharma:  Case Studies - Supporting Industry:  Funding Panel Conference Sessions: 1. Early Discovery 2. Latest Topics in Bioequivalence 3. Successful Candidate Selection from Druggability to Regulatory Submission 4. Regulatory Considerations and Analysis of Subsequent Entry Biologics 5. Nanomedicine 6. Going Beyond Oral Delivery ... Strategies to Enable Drugs to Reach New Targets 7. New Trends in Mass Spectrometry for Drug Discovery & Development 8. Biomarkers in Pharmacotherapy and Drug Development 9. Application of Quality by Design (QbD) and Lifecycle Management to Analytical Procedure 10. Current Topics in Drug Safety 11. Recent Trends in Material and Biomaterial Research